Re-thinking the Life of Constantine-Cyril the Philosopher - Ivanova, M (Modern Humanities Research Association, 2020)
The invention of the Slavonic alphabet is widely celebrated across the Slavonic speaking world today. Due to this, its earliest account, the Life of Constantine-Cyril, has often been assumed to be a Slavonic text, imbued with Slavic patriotism. This article argues that the Life is a profoundly Byzantine text, and that its author was not primarily concerned with the invention of Slavonic. Rather, the text is best understood as an argument about sanctity, and about the harmony between ‘outside’ learning and piety. This argument was constructed with the resources of and was aimed at contemporary Byzantine intellectual culture.